DNA typing in corrections: the FBI's combined DNA index system helps corrections and law enforcement professionals monitor inmates and solve crimes. - Loftus, Patricia (Corrections Today, 1999)
Part of a special section on the use of technology in the corrections profession. The FBI's combined DNA index system (CODIS) is assisting corrections and law enforcement professionals in monitoring inmates and solving crimes. DNA typing strategies allow potential suspects to be eliminated from investigations, and it can also be used to support human identification in a forensic setting. CODIS combines computer technology and forensic science to create a useful tool for solving violent crimes or completing investigative leads. CODIS also provides an electronic link between local, state, and federal crime laboratories for the purpose of exchanging and comparing DNA profiles.